EFFECTIVENESS OF THE MOBILE ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) IN PROSECUTING TRAFFIC VIOLATIONS IN THE JURISDICTION OF THE EAST JAVA REGIONAL POLICE FORCE - Putri, Audita Amanda; Yahman, Dr. Yahman (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2025)
In today's digital era, the police in the traffic sector have developed new innovations in law enforcement against traffic violations through the Electronic Traffic Law Enforcement (ETLE) system. ETLE is divided into two types, which are static ETLE and mobile ETLE. Static ETLE operates using CCTV cameras installed in certain locations, while mobile ETLE is in the form of electronic ticketing cameras installed on police patrol cars to detect traffic violations in real time. However, despite the implementation of the ETLE system, numerous traffic violations still occur in the jurisdiction of the East Java Regional Police. This study aims to examine the legal provisions related to ETLE Mobile as well as the legal sanctions imposed on traffic violators in the implementation of this system in the East Java Police area. This study uses empirical research methods, which are based on field data through observation and interviews. The approaches used include statutory and conceptual approaches, with data sources in the form of primary and secondary legal materials. The results of the study indicate that the system implementation of static and mobile ETLE is still less effective and requires further development. One of the main factors that becomes an obstacle is public awareness, where there are still many individuals who have yet to understand and comply with traffic rules. In addition, factors from law enforcement officials are also influential, such as the limited number of police personnel in the sector of traffic, as well as the lack of socialization and counseling to the public in efforts to prevent traffic violations.